DESAIN MEDIA KARTU REMI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI SATUAN JARAK DAN VOLUME - Prabowo, Alfathius Charol; Sulisawati, Dwi Noviani; Murtinasari, Frida (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study aims to develop learning media in the form of mathematical playing cards on the material of distance and volume units and to determine the level of feasibility and practicality of the developed media. This study uses the research-and-development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. However, the scope of the study is limited to the formative evaluation stage, namely the results of expert validation and teacher responses, without continuing with experimental effectiveness testing. The research subjects included media experts, material experts, and eighth-grade mathematics teachers of SMP Negeri 3 Ambulu. Data collection techniques were carried out through observation, interviews, and validation questionnaires. The data obtained were analyzed descriptively and quantitatively using a feasibility percentage. The results showed that the mathematical playing card media obtained an average value of 88% from media expert validation with a very feasible category. Material expert validation showed an average value of 85% with a feasible to very feasible category, which indicates that the material and questions presented were in accordance with the basic competencies and learning objectives. In addition, teacher responses to the use of the media showed an average value of 90% with a very practical category. Based on these results, it can be concluded that the developed mathematical playing cards media meets the criteria of validity and practicality, so it is suitable for use as a learning medium for the material of distance and volume units for class VIII students of SMP Negeri 3 Ambulu. This media is expected to be an innovative alternative in mathematics learning and can be further developed through further research to test its effectiveness in improving student learning outcomes.